PROFITABILITY AS A MODERATING FACTOR AFFECTING THE VALUE OF ENERGY SECTOR COMPANIES LISTED ON THE IDX - Eliza - Eliza; Fitri Yeni; Annisa Rama Jufri (JURNAL ECONOMICA : Research of Economic And Economic Education, 2025)
This study aims to examine the effect of Investment Opportunity Set, Dividend Policy, and Good Corporate Governance on Firm Value with Profitability as a moderating variable. The population in this study were energy sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. The research sample was selected using a purposive sampling technique, which resulted in 17 energy sector companies with a total of 85 observations. This study uses secondary data and is analyzed using the panel data analysis method. The results of the study indicate that Investment Opportunity Set and Dividend Policy have no effect on Firm Value, while Institutional Ownership has an effect on Firm Value. In addition, Investment Opportunity Set moderated by Profitability has a significant effect on Firm Value in energy sector companies listed on the Indonesia Stock Exchange in the 2019-2023 period. However, Dividend Policy and Institutional Ownership moderated by Profitability have no effect on Firm Value in energy sector companies listed on the Indonesia Stock Exchange in the 2019-2023 period.